Penggantian Gula Kelapa dengan Gula Aren pada Kualitas Kimia Dendeng: Replacement of Coconut Sugar with Palm Sugar on The Chemical Quality of Dendeng - Nilamcaya, Mus; Sari, Novita (Jurnal Riset Agribisnis dan Peternakan, 2022)
Making jerky requires preservatives and flavorers, namely sugar. Sugar is added from brown sugar and palm sugar. The purpose of this study was to see the effect of substitution of coconut sugar and palm sugar on water activity, water content, and jerky yield of laying hens. The treatment of this study substituted coconut sugar and palm sugar up to 30%, which was given was A0K30, A10K20, A20K10, A30K0. The parameters are water activity, moisture content and yield. The substitution of coconut sugar and palm sugar in jerky in water activity ranged from 0.62 to 0.72. The substitution of coconut sugar and palm sugar on water content did not differ markedly in jerky. The substitution of coconut sugar and palm sugar in yield did not differ markedly in afkhir laying hen jerky. The substitution of coconut sugar and palm sugar in jerky in water activity ranged from 0.62 to 0.72. The water content of jerky ranged from 51.8% - 54.7% showed no difference between treatments. The yield of jerky ranged from 51.8±8.98% to 54.7±6.91% also there was no difference between treatments.